Development of MDR-TB Control Model in Northern Thailand - คุณาวรารักษ์ ปิยะดา; จันทร์วงศ์ ศักรินทร์; โพธิแก้ว พัฒนา; ประพันธ์วงค์ อนงค์พร; ศิริ สุนิสา; หุตามัย ทรงวุฒิ; ฤกษ์งาม ศุภชัย (Disease Control Journal, 2010)
Thailand has implemented DOTS strategy to increase TB control program efficacy since 1997. However, Thailand couldn’t achieve key TB control program indicators as indicated by the WHO. The MDRTB rate in northern Thailand has increased above hot spot level. The objective of this study was to compare new MDR-TB control program strategy to the conventional one in upper northern Thailand. We defined two MDR-TB control models. The first model had 3 steps. For step 1, all AFB positive sputum specimens from all hospitals located in 3 upper northern provinces (Chiang Mai, Lumpoon, and Phayao), were screened for Non Tuberculous Mycobacterium. For step 2, all MTB specimens were tested for drug sensitivity testing to identify MDR-TB cases with 1 month turn around time. For step 3, the patients would then be taking care with routine DOTS strategy. There were also 3 steps for the second model. The first two steps were the same as in model 1. But for the third steps, the patients would be communicated via mobile phone from the care giver to remind them about the medication time. In this third step, the MDR-TB patients were randomized to either be in model 1 or model 2. There were at least 19 patients in each arm. We followed the patients 18 months for measuring the treatment outcomes. It was found that the second model had significantly better sputum conversion rates when compared to the first model (p < 0.001). The conversion rates of model 2 were 84.2%, 89.5%, and 100% at month 1, 3, and 5 respectively. For model 1, the conversion rates were 57.9, 73.7, 84.2, and 94.7 at month 1, 2, 3,5 and 9 respectively. The treatment success rate of model 2 (100%) was also significantly higher than model 1 (73.7%) (p = 0.024). The MDR-TB rates in the region were decreased from 4.1% during April-September 2008, to 3.3% during October 2008-March 2009, and to 1.8% during April-September 2009. Successfulness of model 2 could be seen as an important strategy to decrease MDR-TB rate in 3 provinces of northern Thailand below hot spot level within 1 year. The DOT-PLUS strategies together with mobile phone communication as used in model 2 should be promoted in phase manner in order to improve TB control program efficacy. This could lead to achieve the Millennium Development Goals in 2015